2020
DOI: 10.1088/1674-1056/ab84d8
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian entanglement transfer to distant atoms in a coupled superconducting resonator*

Abstract: We investigate the non-Markovian effects on the entanglement transfer to the distant non-interacting atom qubits, which are embedded in a coupled superconducting resonator. The master equation governing the dynamics of the system is derived by the non-Markovian quantum state diffusion (NMQSD) method. Based on the solution, we show that the memory effect of the environment can lead to higher entanglement revival and make the entanglement last for a longer time. That is to say, the non-Markovian environment can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In detail, we would like to mention that in this case, in our calculation for concurrence C BC considering the initial mixed state, two of the eigenvalues for the related matrix are the same. Thus, based on the concurrence relation (15), we achieve C BC = 0, meaning that the qubits B and C are always separable. Furthermore, to deter-mine our calculations, we re-investigate the entanglement of the two qubits B and C when they are initially prepared in a mixed state via the negativity measure and we have obtained the same conclusion with concurrence.…”
Section: The Concurrence For the Initial Mixed Statementioning
confidence: 99%
See 1 more Smart Citation
“…In detail, we would like to mention that in this case, in our calculation for concurrence C BC considering the initial mixed state, two of the eigenvalues for the related matrix are the same. Thus, based on the concurrence relation (15), we achieve C BC = 0, meaning that the qubits B and C are always separable. Furthermore, to deter-mine our calculations, we re-investigate the entanglement of the two qubits B and C when they are initially prepared in a mixed state via the negativity measure and we have obtained the same conclusion with concurrence.…”
Section: The Concurrence For the Initial Mixed Statementioning
confidence: 99%
“…The quantum Fisher information flow may be employed for distinguishing the Markovian and non-Markovian processes. [10,11] Moreover, in particular, the entanglement revives in the non-Markovian regime [9,[12][13][14][15] and reduced exponentially in the Markovian regime. [16][17][18] In fact, even though Markovian dynamics includes a level of back reaction, it neglects the entanglement that arises between bodies and bath modes during the evolution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the memory and feedback effect of non-Markovian reservoirs can reduce the decay of entanglement and enhance the entanglement revival. [27][28][29] The authors in refs. [30][31][32] found that the initial entanglement between the two qubits can be preserved by using the additional qubits.…”
Section: Introductionmentioning
confidence: 99%
“…It holds great physical significance in various functions such as quantum invisible state transfer, quantum key distribution, and quantum dense coding. The coherent state is a continuous variable state closest to the classical light field and photons exhibits a Poisson distribution [1][2][3]. Futhermore, the amplitude and phase defined by the coherent state also satisfy the Heisenberg's uncertainty principle.…”
Section: Introductionmentioning
confidence: 99%